2019
DOI: 10.3390/cells9010069
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cyclic AMP Signaling in Cardiac Fibrosis

Abstract: Myocardial stress and injury invariably promote remodeling of the cardiac tissue, which is associated with cardiomyocyte death and development of fibrosis. The fibrotic process is initially triggered by the differentiation of resident cardiac fibroblasts into myofibroblasts. These activated fibroblasts display increased proliferative capacity and secrete large amounts of extracellular matrix. Uncontrolled myofibroblast activation can thus promote heart stiffness, cardiac dysfunction, arrhythmias, and progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 174 publications
(251 reference statements)
1
47
0
Order By: Relevance
“…However, reduced cAMP levels may mediate alternative consequences in distinct cell types of the myocardium that may not always be favorable. In fibroblasts, diminished cAMP signalling promotes fibrotic effects, cell proliferation and collagen production [149]. In line with these publications, PDE2 overexpression in cardiac fibroblasts accelerated cAMP degradation and subsequently supported fibroblast activation and transformation into myofibroblasts.…”
Section: Fibroblastssupporting
confidence: 59%
“…However, reduced cAMP levels may mediate alternative consequences in distinct cell types of the myocardium that may not always be favorable. In fibroblasts, diminished cAMP signalling promotes fibrotic effects, cell proliferation and collagen production [149]. In line with these publications, PDE2 overexpression in cardiac fibroblasts accelerated cAMP degradation and subsequently supported fibroblast activation and transformation into myofibroblasts.…”
Section: Fibroblastssupporting
confidence: 59%
“…2a) and high cAMP (Fig. 2h) producers 28 , a high concentration of PGE 2 might be necessary to boost additional cAMP production by heart cells in vivo, and this could be a mechanism to prevent excessive activation of cardiac fibroblasts and interstitial fibrosis 28 . On the other hand, high concentrations of PGE 2 are apparently necessary to promote ACh release, as observed in ll1r1 −/− TsV-and PGE 2 -inoculated mice (35 μM/per animal, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-fibrotic effect of cAMP effector molecules PKA and EPAC has been demonstrated in various tissue fibroblasts, including HSCs (reviewed in [ 133 , 134 , 135 ]). Early studies have documented that quiescent HSCs have high levels of pCREB, which decreases upon HSC activation and could be restored with activation of PKA [ 136 , 137 , 138 , 139 ]. Our previous studies demonstrated that primary HSCs do not express cAMP-degrading PDE4 when they are quiescent; however, the expression of three PDE4 subfamilies of proteins, PDE4A, B and D, increases upon the early stage of their activation [ 80 ].…”
Section: Camp Signaling In Aldmentioning
confidence: 99%